(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The psychological relationship between individual and organization hasbeen conceptualized both in terms of identification and in terms of (affective)commitment. In the present study, we explore the differences between these twoconceptualizations. Building on the proposition that identification isdifferent from commitment in that identification reflects the self-definitionalaspect of organizational membership whereas commitment does not, we proposethat commitment is more contingent on social exchange processes that presumethat individual and organization are separate entities psychologically, andmore closely aligned with (other) job attitudes. In support of thesepropositions, results of a cross-sectional survey of university faculty (n=133) showed that identification isuniquely aligned (i.e., controlling for affective commitment) with theself-referential aspect of organizational membership, whereas commitment isuniquely related (i.e., controlling for identification) to perceivedorganizational support, job satisfaction, and turnover intentions. We concludethat the core difference between identification and commitment lies in theimplied relationship between individual and organization: Identificationreflects psychological oneness, commitment reflects a relationship betweenseparate psychological entities. Identification with a psychological group or organization (IDPG) isdefined as the perception of sharing experiences of a focal group and sharingcharacteristics of the group’s members. IDPG is conceptually distinct from therelated concept of organizational commitment. In the present study with 263 employedpersons, IDPG was shown to be empirically distinct from organizationalcommitment. In addition, IDPG was shown to have significantly less overlap thancommitment with three related concepts: job satisfaction, organizationalsatisfaction, and job involvement. This Study attempts to develop a framework for understanding socialidentities by linking together ideas from two disciplines which are normallypursued separately from each other namely, sociology and psychoanalysis.Drawing on the work of Craib (1989, 1994, 1998a) Bion (1961) and Scheff (1994a)in psychoanalysis and Mann (1986, 1993a, 1995, 1997) in sociology, the mainargument is that social identities such as national identity are not just theresult of sociological factors such as social classification, boundaries andprocesses of identification, they also have an important emotional dimensionwhich coexists with but cannot be reduced to the social. In order to understandthe persistence and indeed strengthening of nationalism and national identitiesin the contemporary world, we need to take account not justof changes in the inter-relationships between economics, politics and cultureat the global level, but also of the ways in which they may now be coming tointer-relate with the kind of unconscious psychological processes and strongemotions such as love, hate, shame and anger, which occur within groups. TheStudy begins with a critique of existing sociological approaches to identityfollowed by an attempt to develop an alternative approach based on thepsychoanalytic concept of emotional inter-subjectivity.